2018
DOI: 10.1155/2018/4673061
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Alpha-Tocopherol and Ascorbic Acid to Nonalcoholic Fatty Liver Disease’s Statin Therapy in Men

Abstract: Oxidative stress and inflammation contribute to the pathogenesis and progression of nonalcoholic fatty liver disease (NAFLD), and the control of lipid status by statins may help to stop the progression of NAFLD. We hypothesized that the addition of antioxidant vitamins C and E to atorvastatin therapy is associated with improved serum enzyme antioxidant status. NAFLD-related serum parameters and the activity of antioxidant enzymes, before and after 3 months of treatment, were determined in patients receiving at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Contrary to the PIVENS trial [33], treatment with atorvastatin and vitE alone did not improve ALT and AST. An improvement of AST and ALT was also reported for NAFLD patients receiving 20 mg atorvastatin for 12 weeks, with no additional effect by supplementing the statin with 400 IU vitE and 1000 mg vitC [32], whereas others have reported a reduction in ALT but not AST following six months of statin treatment (10–20 mg) in NAFLD patients [34]. The histological findings from the HF+ animals in the present study supports a state of hepatic stress, and show an increase NAS-score compared to LF and LF+ reaching significance at Week 28.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Contrary to the PIVENS trial [33], treatment with atorvastatin and vitE alone did not improve ALT and AST. An improvement of AST and ALT was also reported for NAFLD patients receiving 20 mg atorvastatin for 12 weeks, with no additional effect by supplementing the statin with 400 IU vitE and 1000 mg vitC [32], whereas others have reported a reduction in ALT but not AST following six months of statin treatment (10–20 mg) in NAFLD patients [34]. The histological findings from the HF+ animals in the present study supports a state of hepatic stress, and show an increase NAS-score compared to LF and LF+ reaching significance at Week 28.…”
Section: Discussionmentioning
confidence: 94%
“…Although no therapy has yet been approved, vitE is recommended for NASH patients and is associated with improvements in histopathological lesions [31]. Alongside vitE supplementation, atorvastatin can be administered to target dyslipidemia in NASH patients and clinical studies have shown beneficial effects of statin treatment on dyslipidemia and markers of hepatic health in patients [32,33,34]. However, comparisons between studies are often challenging due to differences in, e.g., inclusion criterions and intervention time, dose and statin-type.…”
Section: Discussionmentioning
confidence: 99%
“…The human body cannot synthesize vitamin C; a lower consumption of vitamin c has been associated with a decreased plasma level of aa, which may increase the risk of developing metabolic diseases, including naFld/naSH (27). in addition, hepatocytes from patients with naFld/naSH suffer from various types of stress, such as hypoxia, inflammation and er stress (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…as an excellent antioxidant, aa has a wide range of benefits, namely health-promoting and disease-preventing, and therapeutic properties (25). Studies have shown that aa, along with other antioxidants, such as vitamin e, can effectively inhibit oxidative stress, thereby reversing NAFLD (26,27). Apart from its antioxidative activity, aa can protect cells from stress via non-antioxidative pathways (28,29); however, these potential effects of aa alone on naFld/naSH and its mechanisms of action have not yet been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review highlights that since patients with elevated cardiovascular risk require statin treatment, it would be advisable to select a specific statin that provides liver as well as cardiovascular risk reduction [19]. Other studies suggest that proprotein convertase subtilisin kexin type-9 inhibitors ameliorates NAFLD, while the association of antioxidant vitamins C and E with statin therapy in men does not bring any additional benefits [20,21].…”
Section: Resultsmentioning
confidence: 99%